2017
DOI: 10.1186/s13148-017-0371-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation at MHC in CD4+ T cells is associated with multiple sclerosis independently of HLA-DRB1

Abstract: BackgroundAlthough many genetic variants have been associated with multiple sclerosis (MS) risk, they do not explain all the disease risk and there remains uncertainty as to how these variants contribute to disease. DNA methylation is an epigenetic mechanism that can influence gene expression and has the potential to mediate the effects of environmental factors on MS. In a previous study, we found a differentially methylation region (DMR) at MHC HLA-DRB1 that was associated within relapsing-remitting MS (RRMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 19 publications
(28 reference statements)
5
64
3
Order By: Relevance
“…Overall, the PBMC-based methylomes of the 45 MS discordant MZ twins were highly similar, as the mean within-pair β -value differences were very small (<0.05). None of the MS-DMPs observed in our study have previously been reported by other EWAS for MS [19][20][21][22][23][24][25] .…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Overall, the PBMC-based methylomes of the 45 MS discordant MZ twins were highly similar, as the mean within-pair β -value differences were very small (<0.05). None of the MS-DMPs observed in our study have previously been reported by other EWAS for MS [19][20][21][22][23][24][25] .…”
Section: Discussioncontrasting
confidence: 67%
“…However, those MS EWAS studies observed much larger methylation differences and used selection criteria for MS-DMPs of absolute mean β -value differences >0.05 19 , or even >0.10 [20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation is probably the best explored of the three main epigenetic processes, and aberrant methylation in gene regulator regions may underlie processes involved in MS onset . While methylation changes have been reported in MS at HLA‐DRB1 in CD4 + but not CD8 + T cells, in brains, and in relapsing‐remitting versus primary progressive MS, it is unclear if these changes are drivers or responses to the disease.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%